Geology of Honnor Oku-iwa Rock, East Antarctica - Nishida, Tamio; Yanai, Keizo; Kojima, Hideyasu (1982)
P(論文) Honnor Oku-iwa Rock is a small ice-free area located about 6km southeast of Bozu Peak of Byvagasane of central Soya Coast of Lutzow-Holm Bay, East Antarctica, and has been named after the Honnor Glacier of which left margin contacts this rocky area. The result of geological survey of the area is reported in this paper. The crystalline basement of the area comprises the following petrographic types of rock; hornblende gneiss, metabasite, garnet-biotite gneiss and charnockitic rock. A rather small amount of pegmatite intrudes these gneisses. The sequence is about 700m in thickness and probably correlated with the Ongul Group. As a whole the foliation of gneisses dips to the east with moderate to steep angles and the geologic structure is seemingly homoclinal. From the north to the south large sigmoidal configuration of gneisses seems to be caused by one set of synformal and antiformal folds of open type, of which axes both run east-west and slightly plunge to the east. Westerly prolongations of these folds probably can be connected with the open folds in the northern part of the Byvagasane region. The area was once entirely covered by continental ice, and glacial striae and grooves on basement rocks show the east-south-east to west-north-west direction of flow throughout the area. departmental bulletin paper